Pengalaman Memoderasi Penilaian Risiko Kecurangan, Skeptisisme, Beban Kerja pada Kemampuan Mendeteksi Kecurangan - Kiswanto, Kiswanto -; Maulana, Panji Aziz (Jurnal Ilmiah Akuntansi dan Bisnis, 2019)
The purpose of this study was to analyze the effect of fraud risk assessment, skepticism, and workload on the ability to detect fraud with experience as a quasi-moderating variable. The population and sample of this study are auditors who work in the Financial and Development Supervisory Agency (BPKP) of Central Java Province. The sample in this study was 41 auditors. Data collection using a questionnaire. The method of data analysis in this study was moderated regression analysis (MRA). The results showed that fraud risk assessment, skepticism and workload had a significant effect on the ability to detect fraud. Experience could moderate the effect of the relationship between risk assessment of fraud and the ability to detect fraud. Keywords: Risk of fraud assessment, fraud detection, experience